Modulation of Ionotropic Glutamate Receptors and Acid-Sensing Ion Channels by Nitric Oxide - Wang, John Q.; Chu, Xiang-Ping; Guo, Ming-Lei; Jin, Dao-Zhong; Xue, Bing; Berry, Thomas J.; Fibuch, Eugene E.; Mao, Li-Min (Frontiers in Physiology, 2012)
Ionotropic glutamate receptors (iGluR) are ligand-gated ion channels and are densely expressed in broad areas of mammalian brains. Like iGluRs, acid-sensing ion channels (ASIC) are ligand (H+)-gated channels and are enriched in brain cells and peripheral sensory neurons. Both ion channels are enriched at excitatory synaptic sites, functionally coupled to each other, and subject to the modulation by a variety of signaling molecules. Central among them is a gasotransmitter, nitric oxide (NO). Available data show that NO activity-dependently modulates iGluRs and ASICs via either a direct or an indirect pathway. The former involves a NO-based and cGMP-independent posttranslational modification (S-nitrosylation) of extracellular cysteine residues in channel subunits or channel-interacting proteins. The latter is achieved by NO activation of soluble guanylyl cyclase, which in turn triggers an intracellular cGMP-sensitive cascade to indirectly modulate iGluRs and ASICs. The NO modification is usually dynamic and reversible. Modified channels undergo significant, interrelated changes in biochemistry and electrophysiology. Since NO synthesis is enhanced in various neurological disorders, the NO modulation of iGluRs and ASICs is believed to be directly linked to the pathogenesis of these disorders. This review summarizes the direct and indirect modifications of iGluRs and ASICs by NO and analyzes the role of the NO-iGluR and NO-ASIC coupling in cell signaling and in the pathogenesis of certain related neurological diseases.